Entre a astúcia e a vingança: a Inquisição e os colonos na América Portuguesa acusados de blasfemar - Pereira, Diogo Tomaz (Temporalidades, 2015)
ABSTRACT: The Visitations of the Holy Office to Brazil between the sixteenth and eighteenth centuries bring out that both the Portuguese, the Portuguese colonists born in America, had with God, Jesus Christ, the Virgin and the saints, in general, a ratio of great intimacy, and even familiarity, treating them quite often when not meeting them with rudeness and harshness. This article seeks to examine the crimes of blasphemy and heretical propositions occurring in colonial Brazil, presenting the reader with a little history of these two crimes - which can only be treated as one - and the historical actors involved. In addition, supported by the previous discussion, I expose how complex the process was the surgeon Antonio Lobo de Melo, falsely accused of blasphemy and had his life and career "almost" destroyed by the Inquisition of Lisbon, when he was arrested in the city of Rio de Janeiro. KEYWORDS: Blasphemy, False testimony, Portuguese inquisition.